Neutralizing Antibodies Against a Specific Human Immunodeficiency Virus gp41 Epitope are Associated With Long-term Non-progressor Status - Olivier Lucar; Bin Su; Valérie Potard; Assia Samri; Brigitte Autran; Christiane Moog; Patrice Debré; Vincent Vieillard (EBioMedicine, 2017)
Antibodies (Abs) play a central role in human immunodeficiency virus (HIV) protection due to their multiple functional inhibitory activities. W614A-3S Abs recognize a specific form of a highly conserved motif of the gp41 envelope protein and can elicit viral neutralization to protect CD4+ T cells. Here, we describe in detail the neutralizing profile of W614A-3S Abs in untreated long-term non-progressor (LTNP) HIV-infected patients. W614A-3S Abs were detected in 23.5% (16/68) of untreated LTNP patients compared with <5% (5/104) of HIV-1 progressor patients. The W614A-3S Abs had efficient neutralizing activity that inhibited transmitted founder primary viruses and exhibited Fc-mediated inhibitory functions at low concentrations in primary monocyte-derived macrophages. The neutralizing capacity of W614A-3S Abs was inversely correlated with viral load (r = −0.9013; p < 0.0001), viral DNA (r = −0.7696; p = 0.0005) and was associated the preservation of high CD4+ T-cell counts and T-cell responses. This study demonstrates that W614A-3S neutralizing Abs may confer a crucial advantage to LTNP patients. These results provide insights for both pathophysiological research and the development of vaccine strategies.